2003
DOI: 10.2527/2003.8161641x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nutrient utilization, and body composition of dairy calves fed milk replacers containing different amounts of protein1

Abstract: Male Holstein calves < 1 wk of age were allowed a 2-wk adaptation period after purchase, and then were blocked by BW and assigned randomly within block to either a baseline slaughter group or one of four experimental groups (n = 8 to 9 per group). Treatments were isocaloric milk replacers (12.5% solids) fed at 12% of BW that contained 16.1, 18.5, 22.9, or 25.8% CP (DM basis) from whey protein sources. After a 6-wk feeding period, all calves were slaughtered and the weights and chemical composition of the visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
133
6
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 28 publications
35
133
6
6
Order By: Relevance
“…Values for stage 1 are in agreement with earlier reports (Diaz et al, 2001) but are higher than more recent studies (Blome et al, 2003). Values for stages 2 and 3 are consistent with values measured by van den Borne et al (2006) in calves of similar BW.…”
Section: Discussionsupporting
confidence: 92%
“…Values for stage 1 are in agreement with earlier reports (Diaz et al, 2001) but are higher than more recent studies (Blome et al, 2003). Values for stages 2 and 3 are consistent with values measured by van den Borne et al (2006) in calves of similar BW.…”
Section: Discussionsupporting
confidence: 92%
“…Influence of treatment on blood protein fractions Blome et al (2003) The range of mean treatment-related PUN concentrations measured in the current study (2.9 to 3.8 mmol/l), although higher than that (1.0 to 2.1 mmol/l) reported by Blome et al (2003) was comparable to those reported by Terosky et al (1997) and Diaz et al (2001) at 2.5 to 2.9 and 3.3 to 4.7 mmol/l, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…Effects of milk replacer feeding regime Table 5 Summary of studies examining daily liveweight gains during the milk-feeding period Blome et al (2003) and Bartlett et al (2006) in which calves were offered MRs containing up to 260 g CP/kg DM. However, the response to increasing CP content does appear to decline when levels exceed approximately 220 g CP/kg DM as demonstrated by Donnelly and Hutton (1976) and Bartlett et al (2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations